The Relationship of Personal Norms on Pro-Environmental Behaviour among Residents in Johor - zulkipli, hafizah; Nasaruddin, Shafinaz Sofia; yusoff, mohd zarir (Research in Management of Technology and Business, 2023)
The environment plays a vital role in supporting all life forms, including humans, animals, and plants, highlighting its global significance. However, the gap between awareness and action in pro-environmental behavior (PEB) presents a challenge. This study aims to examine the connection between personal norms and PEB in Skudai, Johor Bahru, addressing the limited involvement in environmental initiatives and the difference between values and actions. Conducted in residential areas, the research involves 381 randomly selected residents. Survey questionnaires are used and analyzed with IBM SPSS 26 software. The study emphasizes the advantages of strong personal norms for pro-environmental conduct, underscoring the need to close the awareness-action gap. The findings shed light on the relationship between personal norms and PEB, especially in developed nations. Notably, individuals often behave differently from their values, indicating a need for effective personal norms for environmental responsibility. This highlights the importance of fostering these norms. In conclusion, the research stresses the importance of strengthening personal norms to promote pro-environmental behavior. Addressing the gap between awareness and action is crucial for encouraging sustainable practices and environmental well-being.